2000
DOI: 10.1016/s0014-5793(00)01817-2
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the activity of caspases by L‐carnitine and palmitoylcarnitine

Abstract: L-Carnitine facilitates the transport of fatty acids into the mitochondrial matrix where they are used for energy production. Recent studies have shown that L-carnitine is capable of protecting the heart against ischemia/reperfusion injury and has beneficial effects against Alzheimer's disease and AIDS. The mechanism of action, however, is not yet understood. In the present study, we found that in Jurkat cells, L-carnitine inhibited apoptosis induced by Fas ligation. In addition, 5 mM carnitine potently inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
98
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 37 publications
8
98
1
Order By: Relevance
“…This requires an excess of mitochondrial acetyl-CoA that can be provided by acetyl-L-carnitine. This behavior was similar to hexokinase shunt to increase ADP when ATP synthesis was urgent required [47] Aceyl-L-carnitine be metabolized rapidly when it was injected IV because it was transported to mitochondria directly and acetyl moiety was released into mitochondria by acetyltransferase [38]. This acetyl-CoA was part of acetyl-CoA pool and it participated in the synthesis of glutamate, glutamine, GABA, etc.…”
Section: Nadmentioning
confidence: 79%
See 4 more Smart Citations
“…This requires an excess of mitochondrial acetyl-CoA that can be provided by acetyl-L-carnitine. This behavior was similar to hexokinase shunt to increase ADP when ATP synthesis was urgent required [47] Aceyl-L-carnitine be metabolized rapidly when it was injected IV because it was transported to mitochondria directly and acetyl moiety was released into mitochondria by acetyltransferase [38]. This acetyl-CoA was part of acetyl-CoA pool and it participated in the synthesis of glutamate, glutamine, GABA, etc.…”
Section: Nadmentioning
confidence: 79%
“…In isolated hepatocytes, the addition of L-carnitine did not increase the ß-oxidation but incremented the availability of mitochondrial acylcarnitines [38] suggesting that L-carnitine in normal concentration was sufficient for high ß-oxidation activity. It has also been observed that peroxisomal acylcarnitines can cross to mitochondria by diffusion without CPT1 activation [42] although the metabolic implication of this transport was not quantified.…”
Section: Inhibition Of Apoptosis and Necrosis With Acetyl-l-carnitinementioning
confidence: 89%
See 3 more Smart Citations